Local to global: Working together to meet the needs of vulnerable communities. Issue 5 (3rd September 2017) - Dressel, Anne; Mkandawire-Valhmu, Lucy; Dietrich, Ann; Chirwa, Ellen; Mgawadere, Florence; Kambalametore, Sylvia; Kako, Peninnah
ABSTRACT: Since 2012, the University of Wisconsin–Milwaukee (UWM) faculty from nursing and physical therapy (PT) have been working together towards a common goal: to meet the healthcare needs of vulnerable populations in Malawi and Milwaukee. Sharing valuable knowledge and understanding one another's professions have allowed us to develop interprofessional education (IPE) learning experiences for students to help identify how quality of life could be improved or enhanced for children and their families across two different geographic spaces, one in rural Malawi and the other in urban Milwaukee. IPE learning modules were implemented in UWM's community health-focused short-term study abroad programmes to Malawi. IPE learning modules were also piloted at one of UWM's nurse-managed community health centres, located in a low-income, African American community in the inner city of Milwaukee, Wisconsin. Based on survey data collected from 10 participating IPE students in Milwaukee, from nursing, occupational therapy, PT, and speech and language pathology, a pilot study yielded a statistically significant change in a positive direction for increased understanding of three interprofessional collaborative practice core competencies: values and ethics, roles and responsibilities, and teams and teamwork. In this article, we discuss the processes used to develop, implement, and evaluate IPE experiences for UWM students, which may enable other professionals to envision the various projects they can embark upon from an interprofessional perspective.